ABSORPTION THERMAL COMPRESSORS IN THE SYSTEMS OF COMPLEX POWER SUPPLY OF SEPARATE OBJECTS FROM THE RENEWABLE SOURCES OF ENERGY - Nikolai Ivanovich Stoyanov; Arseny Gennadjevich Stoyanov (Наука. Инновации. Технологии)
The analysis of energy effect absorption thermal compressors in the sys-tems of complex power supply of separate objects from the renewable sources of energy and the feasibility study was performed efficient use of solar energy